Incorporating Non-Unitary Income Elasticities, Choke Prices and Choke Incomes into Applied General-Equilibrium Models - James R. Markusen (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Traditional applied general-equilibrium (AGE) models have always faced trade-offs between analytical and computational tractability and counter-empirical restrictions. One is the assumption of homothetic preferences implying unitary income elasticities of demand, significantly inconsistent with data. Similarly, there is no "choke" income level, below which a certain good is not purchased and there is no choke price above which a good is not purchased, implying no changes in the extensive margin of trade. Here I exploit what I will label a Stone-Geary Modified (SGM) formulation. This produces a model in which there are non-unitary income elasticities, choke income levels for some/all goods, and choke prices. The second approach modifies CRIE (constant relative income elasticity) preferences which are preferred for modeling income elasticities, but don't by themselves permit choke income and prices. While other authors have explored these properties in alternative ways, both my approaches have considerable advantages for high-dimension simulation models in that they retain CES structures and functional forms so that they can slot right into existing modeling formats. They require only small modifications to off-the-shelf cost and expenditure functions, and therefore goods and factor demand functions via Shepard's lemma. Unobserved parameters can be calibrated from observed data and econometric estimates.
Keywords: F10; F17; C63; C68; 330; income elasticities; choke incomes; choke prices; applied general equilibrium